Family business succession planning: Are the outcomes dependent on the predominant gender in the management board? - Rosemarie Kay; André Pahnke; Friederike Welter (Institut für Mittelstandsforschung (IfM) Bonn, 2024)
While existing research on business successions stresses the importance of the economic situation of family business in this context, research on women's entrepreneurship, however, suggests that women-led businesses may be less economically attractive for potential successors because of structural differences in comparison to men-led business. Moreover, the business owner's gender may have an impact on the business succession process and its outcome too. Based on one the largest German establishment surveys which is augmented by additional administrative data, this chapter seeks to further link the two research strands by providing first insights into the impact of family businesses owner's gender on both business succession planning and the outcome of the business succession process. Regarding the outcome of business successions, the results indicate that differences between women- and men-led businesses are not related to gender but to characteristics of the businesses to be handed over.
Keywords: J16; L26; M2; 330; Gender; family businesses; business succession